2006
DOI: 10.1105/tpc.105.037192
|View full text |Cite
|
Sign up to set email alerts
|

AUXIN RESPONSE FACTOR8Is a Negative Regulator of Fruit Initiation inArabidopsis 

Abstract: Fruit and seed formation in plants is normally initiated after pollination and fertilization, and, in the absence of fertilization, flowers senesce. In the Arabidopsis thaliana mutant fruit without fertilization, a mutation in AUXIN RESPONSE FACTOR8 (ARF8) results in the uncoupling of fruit development from pollination and fertilization and gives rise to seedless (parthenocarpic) fruit. Parthenocarpy was confirmed in two additional recessive alleles and was caused by mutations within the coding region of ARF8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
223
1
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(252 citation statements)
references
References 78 publications
4
223
1
13
Order By: Relevance
“…In view that Arabidopsis AtARF1 and AtARF2 participate in the regulation of seed size and weight Schruff et al, 2006), combined with the occurrence of CsARF01 and CsARF07 mRNA transcripts in fruit, we propose that CsARF01 and CsARF07 play similar roles in cucumber seed development. Similarly, the possible functions of CsARF02 and CsARF09 in flower maturation like its sister pair members AtARF06 and AtARF08 (Goetz et al, 2006), CsARF05 in vascular development like AtARF05 (Hardtke and Berleth, 1998;Vidaurre et al, 2007), CsARF12 in leaf identity and morphogenesis like AtARF04 (Hunter et al, 2006), and CsARF15 in root development like AtARF17 were expected (Rhoades et al, 2002). The 1:n (AtARF09/CsARF06/CsARF08) and n:1 (AtARF19/CsARF03/AtARF07) orthologous relationships in Arabidopsis and cucumber ARF members suggested that function might have begun to diversify in one species due to gene duplication (Wang et al, 2007;Wu et al, 2011).…”
Section: Phylogenetic Relationship Between Csarf Atarf Osarf and Zmentioning
confidence: 99%
See 1 more Smart Citation
“…In view that Arabidopsis AtARF1 and AtARF2 participate in the regulation of seed size and weight Schruff et al, 2006), combined with the occurrence of CsARF01 and CsARF07 mRNA transcripts in fruit, we propose that CsARF01 and CsARF07 play similar roles in cucumber seed development. Similarly, the possible functions of CsARF02 and CsARF09 in flower maturation like its sister pair members AtARF06 and AtARF08 (Goetz et al, 2006), CsARF05 in vascular development like AtARF05 (Hardtke and Berleth, 1998;Vidaurre et al, 2007), CsARF12 in leaf identity and morphogenesis like AtARF04 (Hunter et al, 2006), and CsARF15 in root development like AtARF17 were expected (Rhoades et al, 2002). The 1:n (AtARF09/CsARF06/CsARF08) and n:1 (AtARF19/CsARF03/AtARF07) orthologous relationships in Arabidopsis and cucumber ARF members suggested that function might have begun to diversify in one species due to gene duplication (Wang et al, 2007;Wu et al, 2011).…”
Section: Phylogenetic Relationship Between Csarf Atarf Osarf and Zmentioning
confidence: 99%
“…Classical genetic strategies have led to the identification of ARF gene roles in plant growth and development. For instance, arf mutations result in the suppression of the hookless phenotype and hypocotyl bending (AtARF2) (Sessions et al, 1997;Ellis et al, 2005;Schruff et al, 2006), defects in flower formation and patterning (AtARF3) (Nemhauser et al, 2000;Nishimura et al, 2005), abnormal vascular development and embryo axis formation (AtARF5) (Hardtke and Berleth, 1998;Vidaurre et al, 2007), impaired hypocotyl response to blue light, growth and auxin sensitivity (AtARF7) (Harper et al, 2000;Tatematsu et al, 2004), delayed fruit development and seed formation (AtARF8) (Goetz et al, 2006), and resistance to auxin and ethylene treatments (AtARF19) (Li et al, 2006). Moreover, phenotypes of double mutants for some sister pairs of ARF, e.g., AtARF1/ AtARF2, AtARF3/AtARF4, AtARF5/ATARF7, AtARF6/AtARF8, and AtARF10/AtARF16, are more severe than the single mutant Nagpal et al, 2005;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings suggest the ability of auxin to regulate sugar accumulation during fruit development via SlARF4. A number of studies have demonstrated the role of specific ARFs in early stages of fruit development such as fruit set (Wang et al, 2005;Goetz et al, 2006;de Jong et al, 2009b), but the putative role of these transcriptional regulators in controlling some ripening-related events and the overall quality of the fruit remains largely unknown.…”
mentioning
confidence: 99%
“…The P1/HC-Pro/GUS/hpGUS line is hemizygous for the P1/HC-Pro transgene and was previously published as P1/ HC-Pro/6b4/306 (Mlotshwa et al, 2008). The arf8-6 line is the University of Wisconsin T-DNA line WiscDsLox324F09 (Goetz et al, 2006). The arf8-8 line has an ethyl methane sulfonate-generated G to A mutation in a splice acceptor site in ARF8 (Reeves et al, 2012).…”
Section: Arabidopsis Linesmentioning
confidence: 99%